2019
DOI: 10.24843/pastura.2018.v07.i02.p06
|View full text |Cite
|
Sign up to set email alerts
|

Kemadirian Pakan Berbasis Hijauan Lokal Untuk Kerbau Di Provinsi Banten

Abstract: ABSTRAKHijauan merupakan pakan utama ternak kerbau di peternakan rakyat. Kebutuhan hijauan pakan akan meningkat seiring tuntutan peningkatan populasi kerbau. Kerbau dipelihara secara semi intensif di padang penggembalaan alam, pekarangan dan terintegrasi dengan lahan pertanian. Ketersediaan hijauan untuk kerbau rendah pada musim kemarau. Tujuan penelitian adalah mengukur potensi hijauan pakan dan strateginya untuk kemandirian pakan hijauan bagi kerbau di Provinsi Banten. Penelitian dilaksanakan di padang pengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Research conducted by Prihantoro et al (2018) found that the botanical composition value of buffalo grazing areas varied with the main vegetation dominance being grass species (56.55 -95.94%). Sudarman et al (2019) found that the traditional feeding system applied by farmers for their buffaloes in the form of only rice straw and grass, although given ad libitum, could not increase the body weight of livestock.…”
Section: Figure 1 Botanical Composition Of Forage In Buffalo Rearing ...mentioning
confidence: 99%
“…Research conducted by Prihantoro et al (2018) found that the botanical composition value of buffalo grazing areas varied with the main vegetation dominance being grass species (56.55 -95.94%). Sudarman et al (2019) found that the traditional feeding system applied by farmers for their buffaloes in the form of only rice straw and grass, although given ad libitum, could not increase the body weight of livestock.…”
Section: Figure 1 Botanical Composition Of Forage In Buffalo Rearing ...mentioning
confidence: 99%